KETAHANAN PANGAN DAN MEKANISME KOPING RUMAH TANGGA PETANI PADI SAWAH LEBAK BERDASARKAN STATUS KEPEMILIKAN LAHAN - Yunita, Yunita; S, Basita Ginting; Asngari, Pang S; Susanto, Djoko; Amanah, Siti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
Fulfilling of household food security of lowland rice farmers require sufficient capacities to improve their productivity and income. Nowadays, lowland rice farmers are in difficult conditions and at risk to food security. This research aimed to analyze capacity, food security level, and copying mechanism of lowland rice farmer’s household based on land property right and to analyze the correlation between capacity and food security of lowland rice farmer’s household. This research utilized survey method on 200 lowland rice farmers household at Ogan Ilir and Ogan Komering Ilir District, South Sumatera. The data were analyzed by descriptive and Chi-square test. The results showed that the farmer’s capacities level was at middle category, the farmers’ household food security level was low, and coping mechanism of the farmers household was at high category. There was no significant correlation between capacity and food security of the lowland rice farmers household (p>0,05) also was found in this research.